2017
DOI: 10.1155/2017/8921932
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy in Parkinson’s Disease: Building ParkinsonNet in Czechia

Abstract: Objective We conducted a questionnaire survey to investigate the availability and quality of physiotherapy (PT) for Parkinson's disease (PD). Background Despite evidence about the benefits of PT, there is no data regarding its use in Czechia. Methods Questionnaires were sent to 368 PD patients seen in a single movement disorders centre within two years (inclusion criteria: idiopathic PD, Hoehn and Yahr stage <5, and residence in Prague) and to 211 physical therapists (PTs) registered in Prague. The patient que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
3
1
1
Order By: Relevance
“…For example, only 14.8% of PwP in our study utilized physical therapy. This is in the lower range of rates previously reported in other countries, which ranged for physical therapy from 14% in the United States to 60% in the Netherlands [ 18 , 43 45 ]. Among the services on which participants reported, physical therapy had the highest utilization rate, while hydrotherapy, occupational therapy, and speech and language pathology had substantially lower rates.…”
Section: Discussioncontrasting
confidence: 56%
“…For example, only 14.8% of PwP in our study utilized physical therapy. This is in the lower range of rates previously reported in other countries, which ranged for physical therapy from 14% in the United States to 60% in the Netherlands [ 18 , 43 45 ]. Among the services on which participants reported, physical therapy had the highest utilization rate, while hydrotherapy, occupational therapy, and speech and language pathology had substantially lower rates.…”
Section: Discussioncontrasting
confidence: 56%
“…O presente estudo identificou a necessidade de mais pesquisas sobre o assunto, visto que apesar de ter modelos de pesquisas relacionados 15,16 , estes possuem objetivos e instrumentos diferentes 15,17,18,19 , demonstrando uma escassez de estudos na literatura principalmente sobre a escala SATIS-BR nessa população, bem como no modelo de intervenção. Pode-se ainda reforçar a relevância de programas terapêuticos alternativos e dinâmicos que busquem o aumento da atividade física e o cuidado psicoterapêutico, visto que estes podem estar correlacionados com processos neurofisiológicos positivos 15 .…”
Section: Discussionunclassified
“…In other countries, specific information on rehabilitation therapy use in PD patients is limited. In the Czech Republic, a survey of PD patients from 2013 to 2015 at a single hospital reported that 28% had received physiotherapy prescribed for PD [ 35 ]. The authors claimed that implementation of the European physiotherapy guideline for PD and the introduction of an efficient model of care such as ParkinsonNet are needed.…”
Section: Rehabilitation Usagementioning
confidence: 99%